Newly Diagnosed Monostotic Paget’s Disease of Bone during Living Kidney Donor Candidate Evaluation - Diana Jędrzejuk; Paweł Poznański; Paweł Szewczyk; Oktawia Mazanowska; Marek Bolanowski; Magdalena Krajewska; Dorota Kamińska (Biomedicines, 2023)
The popularity of living-donor organ donation has increased recently as an alternative to deceased-organ donation due to the growing need for organs and a shortage of deceased-donor organs. This procedure requires an in-depth health assessment of candidates, who must be in excellent physical and mental health. We present a potential living-kidney donor withdrawn from donation due to a newly diagnosed Paget’s disease of bone (PDB). The patient underwent computed tomography (CT), magnetic resonance imaging (MRI), bone scintigraphy, and bone densitometry with trabecular bone score (TBS) assessment. The sole lumbar vertebra affected by PDB was investigated comprehensively, non-invasively, quantitatively, and qualitatively.